Uniportal video-assisted thoracic surgery course in Mexico—first experience - Céspedes-Meneses, Erick; Echavarri-Arana, José Manuel; Tort-Martínez, Alejandro; Guzmán-de Alba, Enrique; Neves-Pereira, Joao Carlos das; González-Rivas, Diego (Journal of Visualized Surgery; Vol 2 (August 2016): Journal of Visualized Surgery, 2016)
“The First Minimally Invasive Thoracic Surgery Uniportal Course” in Mexico was held from July 13th to 15th in Mexico City, at the National Institute of Respiratory Diseases (INER). Thoracic surgeons from around Mexico assisted the course. The special guests were the Spanish doctor Diego González-Rivas and the Brasilian doctor Joao Carlos das Neves-Pereira. The course included live surgery and wet lab. Demonstration of the uniportal video-assisted thoracic surgery (VATS) technique was done. The course was a success and Mexican thoracic surgeons were ready to adopt this technique.